2016
DOI: 10.1016/j.phymed.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective effects of (−)-α-bisabolol against ischemic-reperfusion acute kidney injury

Abstract: (-)-α-Bisabolol has a nephroprotective effect in kidney I/R, with antioxidant effect. Moreover, this result seems to be associated to a direct protective effect on tubular epithelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
2
22
0
1
Order By: Relevance
“…In this study, we observed the increase in MDA levels ( Fig. 2E) related to the AKI onset, as shown previously by Da Costa et al 2015, Sampaio et al (2016) and Kadkhodaee et al (2014). MDA and GSH levels were measured in renal tissue to indirectly assess oxidative stress.…”
Section: Resultssupporting
confidence: 87%
“…In this study, we observed the increase in MDA levels ( Fig. 2E) related to the AKI onset, as shown previously by Da Costa et al 2015, Sampaio et al (2016) and Kadkhodaee et al (2014). MDA and GSH levels were measured in renal tissue to indirectly assess oxidative stress.…”
Section: Resultssupporting
confidence: 87%
“…It showed the ability to lessen oxidative stress and delay the development of various disease complications by countering ROS production as in isoproterenol-induced myocardial infarction [68]. Moreover, (−)-α-bisabolol has exhibited in vivo and in vitro nephroprotective activity in kidney ischemic-reperfusion models in vivo, through the attenuation of functional alterations and reduction of lipid peroxidation and urinary kidney injury molecule-1 (uKIM-1) levels, which was associated with an improvement of GSH levels in male Wistar rats, and in vitro through enhancing cell viability and decreasing ROS production in Rhesus Monkey Kidney Epithelial Cells (LLC-MK2 cells) [69] and inhibiting NADPH oxidase enzyme activity in HK2 cells [70]. In addition, cinnamaldehyde inhibits ROS production in association with the up-regulation of the antioxidative enzyme heme-oxygenase 1 (HO-1).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were incubated in the dark for 30 min, washed twice with PBS, and re-suspended in PBS (500 µL/tube). Finally, the samples were analyzed using flow cytometry [73]. Results were evaluated using relative fluorescent intensity, calculated as described in the previous item.…”
Section: Methodsmentioning
confidence: 99%